The predictability of Malaysia crude oil production using Box-jenkins autoregressive integrated average (ARIMA) model / Zamzulani Mohamed, Nazuha Muda @ Yusof and Ruzaidah Sulong @ A. Rashid - Mohamed, Zamzulani; Muda @ Yusof, Nazuha; Sulong @ A. Rashid, Ruzaidah (2010)
This study examines the Box-Jenkins Autoregressive Integrated Moving Average (ARIMA) in forecasting crude oil production. Monthly Malaysia crude oil production data for the period of January 2005 to May 2010 were analyzed using time-series method that consists of model identification, model estimation and diagnostic checking. Autocorrelation and partial autocorrelation functions were calculated to examine the stationarity of the data. Then, an appropriate Box-Jenkins ARIMA model was fitted. Validity of the model was tested using Ljung-Box statistic technique. The forecasts are derived from the best ARIMA model to predict future Malaysia Crude Oil Production for the period of June 2010 to August 2010. Our 'result on the prediction showed that the trend of Malaysian Crude Oil Production will exhibit to increase with light fluctuation for three leading months.